Fertilizing with native efficient microorganisms has a positive effect on the phenology, biomass and production of tomato (Lycopersicum esculentum Mill) - Alarcon, Juan (2020)
The objective of this research was to evaluate the influence of autochthonous efficient microorganisms (AEM) on the cultivation of Lycopersicum esculentum Milll (tomato) variety "Río Grande". The experiment was conducted in San Gabriel, Apurímac, Peru. The factors studied were doses (12.5, 25 and 50 cc) and application frequencies (7, 14 and 21 days); a randomized complete block design was used, with a factorial arrangement of 3 x 3 + 1, with three repetitions. Plant height, number of flowers, leaf area, number of stems, root weight and yield in g/plant were evaluated. The results showed that the dose of 25 cc of AEM applied every 14 days, contributed to a higher height (39 cm), higher number of flowers (37 flowers), higher leaf area (24 cm2), higher number of stems per plant (5 stems), higher weight of the root at harvest (59.67 g) and higher yield (1713.69 g/plant). This suggests that the application of biofertilizer can be an important alternative to fertilize crops such as tomatoes, reducing the use of chemical synthesis fertilizers and increasing production.